2023
DOI: 10.1038/s41467-023-36681-z
|View full text |Cite
|
Sign up to set email alerts
|

Intra-pituitary follicle-stimulating hormone signaling regulates hepatic lipid metabolism in mice

Abstract: Inter-organ communication is a major hallmark of health and is often orchestrated by hormones released by the anterior pituitary gland. Pituitary gonadotropes secrete follicle-stimulating hormone (FSH) and luteinizing hormone (LH) to regulate gonadal function and control fertility. Whether FSH and LH also act on organs other than the gonads is debated. Here, we find that gonadotrope depletion in adult female mice triggers profound hypogonadism, obesity, glucose intolerance, fatty liver, and bone loss. The abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The FSHβ protein can freely diffuse into prokaryotic cells after its expression. In the prediction of subcellular localization, our results indicated that FSHβ protein was also expressed in the nucleus (Liu et al 2020;Tian et al 2023). In addition, further prediction using TMHMM confirmed that there was no obvious transmembrane domain and signal peptide distribution in the FSHβ protein (Palmerini et al 2016;Niu et al 2019).…”
Section: Discussionmentioning
confidence: 63%
“…The FSHβ protein can freely diffuse into prokaryotic cells after its expression. In the prediction of subcellular localization, our results indicated that FSHβ protein was also expressed in the nucleus (Liu et al 2020;Tian et al 2023). In addition, further prediction using TMHMM confirmed that there was no obvious transmembrane domain and signal peptide distribution in the FSHβ protein (Palmerini et al 2016;Niu et al 2019).…”
Section: Discussionmentioning
confidence: 63%
“…The explanation given here is similar to that of the pancreas: the structure and function of endocrine cells in the same gland affect the function of other endocrine cells. 40 In addition, the effects of FSH on hepatic lipid metabolism show gender dimorphism, and this study failed to detect FSHR in the pituitary gland of male mice, explaining why FSH does not regulate hepatic steatosis in male mice. In conclusion, FSH may affect lipid metabolism through paracrine effects outside the HPG axis, making it difficult to define the therapeutic value of FSH agonists or inhibitors for metabolic syndrome.…”
Section: Hpg Axis and Hepatic Lipid Homeostasismentioning
confidence: 67%
“…A recent study has revealed a third possible mechanism by which FSH affects liver lipid metabolism. This study revealed that the paracrine action of FSH on pituitary corticotropes can serve as a mechanism to inhibit the synthesis of corticosterone and protect against hepatic steatosis [ 38 ]. The fourth possible reason may be associated with inhibin A.…”
Section: Discussionmentioning
confidence: 99%